Northwoods Vernacular Region as Defined by Hydrology and Sportsmen's Activities - Schulz, Roger (My University, 2010)
For many Americans the northern part of Wisconsin, Michigan, and Minnesota holds something extraordinarily special. Among the trees, lakes, rivers, and streams there is a common belief declaring this a unique region in our majestic country. Therefore, what constitutes the Northwoods as a unique region is what guided this research endeavor. As fishing and hunting are seen as a unique component of the Northwoods, we applied fishing and hunting license sales per county, and lakes with lodges and resorts on them to define the Northwood?s as a region.
Color poster with text, charts, and maps.
Keywords: Northwoods Region--Geography; Northwoods Region--Social life and customs; Regionalism--Minnesota; Regionalism--Wisconsin; Regionalism--Michigan; Posters